2006
DOI: 10.1111/j.1467-8624.2006.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Interactions With Latino Infants: Variation by Country of Origin and English Proficiency

Abstract: This study examined variation in mother-infant interactions, father engagement, and infant cognition as a function of country of origin, socioeconomic status, and English language proficiency in a national sample of Latino infants (age 9 months) born in the United States and living with both biological parents (N=1,099). Differences between Mexican-American infants, who had lower mother-infant interaction scores and less father physical play than did the other Latino infants, were associated with differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 63 publications
(71 reference statements)
7
124
0
1
Order By: Relevance
“…Many studies have found healthier behaviors in less acculturated and limitedEnglish-proficient Latinos. 10,13,14 Two studies have suggested that either lower acculturation levels or Spanish language preference are associated with less TV viewing. 15,33 Language use or proficiency may reflect different sociocultural contexts including varying access to media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found healthier behaviors in less acculturated and limitedEnglish-proficient Latinos. 10,13,14 Two studies have suggested that either lower acculturation levels or Spanish language preference are associated with less TV viewing. 15,33 Language use or proficiency may reflect different sociocultural contexts including varying access to media.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,14 Prior work has shown increased television viewing in children of English-speaking compared to Spanish-speaking Latina mothers in children less than 3 years of age. 15 This may reflect the relationship of English language proficiency with varying sociocultural characteristics and contexts.…”
mentioning
confidence: 99%
“…A recent study found couple conflict to be associated with decreased parental emotional availability, which led to an insecure representation of the parent-child relationship (Sturge-Apple, Davies, Winter, Cummings, & Schermerhorn, 2008). Couple conflict has also been linked to spanking (Black, Dubowitz, & Starr, 1999;Cabrera, Shannon, West, & Brooks-Gunn, 2006) and increased hostility directed to children by both mothers and fathers (Harold, Elam, Lewis, Rice, & Thapar, 2012).…”
Section: Factors Influencing Parentingmentioning
confidence: 94%
“…These findings are somewhat consistent with previous research with Hispanic fathers. For example, Cabrera et al (2006) examined Hispanic fathers' engagement in literacy, caregiving, and physical play in relation to Hispanic infants' overall mental development. They found that there was no relation between Hispanic fathers' engagement in literacy, caregiving, and physical play and infants' mental=cognitive development.…”
Section: Fathers' Home Literacy Involvement Predicts Preschool Math Amentioning
confidence: 99%